2018
DOI: 10.7874/jao.2017.00374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Dizziness Associated with Acute Peripheral Facial Palsy

Abstract: Background and ObjectivesWe aimed to assess the clinical significance of dizziness associated with acute peripheral facial palsy (APFP).Subjects and MethodsMedical records of patients who visited an otorhinolaryngology clinic at a university hospital and were admitted for treatment of APFP between 2014 and 2016 were thoroughly reviewed.ResultsIn total, 15.3% (n=15) of patients had dizziness. Continuous, rotatory dizziness without exacerbating factors was most common and frequently accompanied by nausea/vomitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
1
7
0
5
Order By: Relevance
“…Surprisingly, cerebrospinal analysis in the present study, performed in 79 dogs with suspected IVS, revealed only mild mixed pleocytosis in 2 dogs and albuminocytological dissociation in 4 dogs. In human patients presenting with acute facial neuropathy, 15% report associated dizziness [20] and spontaneous nystagmus is also seen in approximately one third of patients with Bell's palsy (a peripheral-type facial nerve paralysis) most commonly associated with reactivation of herpes simplex virus type 1 [21]. The most common cause for vestibular and concurrent facial nerve impairment in people is a viral inflammation caused by Herpes zoster oticus, which generally also causes severe hearing loss and does not typically resolve with corticosteroids or antiviral drugs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, cerebrospinal analysis in the present study, performed in 79 dogs with suspected IVS, revealed only mild mixed pleocytosis in 2 dogs and albuminocytological dissociation in 4 dogs. In human patients presenting with acute facial neuropathy, 15% report associated dizziness [20] and spontaneous nystagmus is also seen in approximately one third of patients with Bell's palsy (a peripheral-type facial nerve paralysis) most commonly associated with reactivation of herpes simplex virus type 1 [21]. The most common cause for vestibular and concurrent facial nerve impairment in people is a viral inflammation caused by Herpes zoster oticus, which generally also causes severe hearing loss and does not typically resolve with corticosteroids or antiviral drugs [22].…”
Section: Discussionmentioning
confidence: 99%
“…The following conditions were reported to be related to the occurrence of facial palsy ( Table 1 ). 1 5 6 7 11 14 15 …”
Section: Resultsmentioning
confidence: 99%
“…The most common disease causing peripheral facial nerve palsy is idiopathic Bell's palsy. 1 For the pathogenesis of idiopathic Bell's palsy, reactivation of Herpes simplex virus type 1 is presumed to be the most relevant infection. Other viral infections such as varicella zoster virus and human herpes virus 6 are quite common.…”
Section: Introductionmentioning
confidence: 99%
“…Pode-se utilizar para o diagnóstico mais preciso a reação em cadeia da polimerase (PCR) pois permite a identificação do genoma do VVZ, porém não pode fazer um diagnóstico com rapidez no início dos sintomas. Por isso o citodiagnóstico de Tzanck é mais útil e rápido em casos de emergência (Magalhães et al, 2014;Paiva et al, 2017;Song et al, 2018;Kim et al, 2021;Pupic-Barack et al, 2021). Além disso, a paciente realizou uma ressonância magnética de crânio que apresentou um discreto favorecimento a possibilidade de um processo inflamatório/infeccioso do nervo facial direito (neurite).…”
Section: Discussionunclassified